The influence of self-esteem, depression, and life satisfaction on the future expectations of Peruvian university students - Mamani-Benito, Oscar; Carranza Esteban, Renzo Felipe; Caycho-Rodríguez, Tomás; Castillo-Blanco, Ronald; Tito-Betancur, Madona; Alfaro Vásquez, Rosa; Ruiz Mamani, Percy G. (Frontiers in Education, 2023)
Introduction Strengthening the self-confidence of future professionals can help them achieve professional goals with a likelihood of being able to achieve them in the future. The objective was to determine whether self-esteem, depression, and life satisfaction influence the future expectations of Peruvian university students. Methods A total of 708 university students participated (64.8% were female, mean age = 21.49; SD = 4.83). The Rosenberg Self-Esteem Scale, the Patient Health Questionnaire-2, the Life Satisfaction Scale, and the Adolescent Future Expectations Scale were used. Structural equation modeling was employed to test the impact of selfesteem, depression, and life satisfaction on future expectations. Results The model relating the study variables demonstrated an adequate fit (p < 0.001, CFI = 0.940, RMSEA = 0.073), confirming the relationship between self-esteem (β = 0.33, p < 0.001), life satisfaction (β = 0.28, p < 0.001), and depression (β = −0.14, p < 0.010.) with future expectations. This model explained 36% of future expectations. Discussion In conclusion, future expectations may be affected by low levels of self-esteem and life satisfaction and high levels of depression.